THE TRADITION OF LARUNG LAUT FROM THE PERSPECTIVES OF SUFI AND MUTAKALLIMIN - Sahri Sahri (Al-Qalam, 2022)
Indonesian society, especially in Java, which is predominantly Muslim, has not yet been able to leave local traditions and culture. The acculturation of Islam and local culture produces a variety of religiosity that is unique and different from Muslim religiosity in other places. This tradition and culture are highly respected by the Javanese people, one of which is the Larung Laut tradition which is held by the fishing community as a form of gratitude and a request for safety to the rulers of the sea. The purpose of this article was to examine the tradition of Larung Laut from Sufi and Mutakallimin perspectives, using a phenomenological approach, descriptive qualitative method. The results of this study were: The Sufi perspective, a form of expressing gratitude for the abundance of blessings from God and being patient for sacrificial offerings displayed through the Larung Laut ceremony is one of the signs of Zuhud's nature. In addition, it also implied the values of Khauf (fear of Allah by having feelings of worry about the punishment of Allah that will be bestowed upon us), as well as the values of Raja' (expecting pleasure, mercy and help from Allah). Meanwhile, the perspective of Ahlussunah Wal Jamaah found that: Elements in the Javanese Larung Laut tradition that have polytheistic values must be removed; Larung Laut which has been internalized with Islamic values is an Islamic act, and is allowed, there is no element of shirk, superstition, and superstition; as well as the symbols contained in the Larung Laut tradition which are required for meaning and philosophy are part of the richness of Javanese culture that needs to be preserved, because it is the way of the previous elders in educating the next generations to be better and civilized